2009
DOI: 10.2118/109018-pa
|View full text |Cite
|
Sign up to set email alerts
|

Artificial-Intelligence Technology Predicts Relative Permeability of Giant Carbonate Reservoirs

Abstract: Summary Determination of relative permeability data is required for almost all calculations of fluid flow in petroleum reservoirs. Water/oil relative permeability data play important roles in characterizing the simultaneous two-phase flow in porous rocks and predicting the performance of immiscible displacement processes in oil reservoirs. They are used, among other applications, for determining fluid distributions and residual saturations, predicting future reservoir performance, and estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…The COD and total suspended solids (TSS) data have magnitudes within the order of 10,000, while for the dissolved oxygen (DO) the magnitude is much lower and in the order of 0.1. To normalise the data the minimax function was applied, as this normalises the variables without any loss of information [6]. The equation to normalise the data is given below:…”
Section: Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…The COD and total suspended solids (TSS) data have magnitudes within the order of 10,000, while for the dissolved oxygen (DO) the magnitude is much lower and in the order of 0.1. To normalise the data the minimax function was applied, as this normalises the variables without any loss of information [6]. The equation to normalise the data is given below:…”
Section: Data Processingmentioning
confidence: 99%
“…[5]. Often the bioprocess parameters are not known but the volume of data is considered sufficient to assume that the model data statistics equate to the bioprocess parameters [6]. This assumption fails if the data does not represent the whole system due to temporal influences being limited, so variability in the data is not fully realised.…”
Section: Introductionmentioning
confidence: 99%
“…The extracted features were normalised to ensure all variables were given equal weight by the classification algorithms. To normalise without any loss of information the minimax function was applied [28]. For each cultivar data set, the data was partitioned into training (80%) and testing (20%) data sets.…”
Section: Machine Learning Classification Modelsmentioning
confidence: 99%
“…Artificial intelligence techniques and ANNs in particular are fast and accurate methods for predicting reservoir properties, and can be applied in reservoir modelling and characterization . Moreover, neural networks have quickly gained popularity and fame in solving complex nonlinear problems . Numerous studies have reported successful implementations of neural network techniques for solving petroleum industry problems .…”
Section: Introductionmentioning
confidence: 99%
“…[25] Moreover, neural networks have quickly gained popularity and fame in solving complex nonlinear problems. [25][26][27][28] Numerous studies have reported successful implementations of neural network techniques for solving petroleum industry problems. [29][30][31] Recently, some new neural network systems have been employed to solve important problems in the industry.…”
Section: Introductionmentioning
confidence: 99%